2002
DOI: 10.1525/si.2002.25.4.515
|View full text |Cite
|
Sign up to set email alerts
|

Slaps, Punches, Pinches—But not Violence: Boundary‐Work in Nursing Homes for the Elderly

Abstract: This article presents an analysis of boundary work in the context of care for the elderly, where violence appears to be widespread but is still relatively unacknowledged. Talk about aggressive patients was formulated in a particular way among workers in a nursing home. Nursing home staff described how the elderly residents sometimes slapped, pinched, or hit them. Although staff members could describe these acts as intentional, although they could hold patients responsible, and although this violence could end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 37 publications
0
61
0
7
Order By: Relevance
“…Emotional bonds between resident and staff are reinforced by family ideology (Dodson and Zincavage 2007), which encourages staff to view residents as if they are part of a family. In a set of observations closer to the agenda of this article, Akerstrom’s (2002) study of boundary work in nursing homes found that staff endure slaps, punches, and scratches, but do not think of them as “violent” as a strategy to preserve boundaries between staff as care givers, residents as care takers, and nursing homes as caring places.…”
Section: Theoretical Frameworkmentioning
confidence: 92%
“…Emotional bonds between resident and staff are reinforced by family ideology (Dodson and Zincavage 2007), which encourages staff to view residents as if they are part of a family. In a set of observations closer to the agenda of this article, Akerstrom’s (2002) study of boundary work in nursing homes found that staff endure slaps, punches, and scratches, but do not think of them as “violent” as a strategy to preserve boundaries between staff as care givers, residents as care takers, and nursing homes as caring places.…”
Section: Theoretical Frameworkmentioning
confidence: 92%
“…This situation could be applied to the nursing home setting where older people who may have lived alone for many years are exposed to interactions among many individuals, both residents and staff in crowded spaces. Any hostile and aggressive interactions can create an environment where all participants are at increased risk of being an abuse victim (Akerstrom, 2002). Cognitive impairment of both victim and perpetrator has been identified as an important potential risk factor for R-REM in long term care.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, the jurisdictional boundaries are not the only lines of demarcation that are of importance for professional groups. Other types of boundaries with relevance to professions concern, among other things, identity, knowledge, autonomy, discretion, and valued objects (Bechky, 2003;MacLure, 1996;Norris, 2001;Åkerström, 2002). While, for the purposes of analysis, these boundaries can be separated, in reality they are immanently intertwined.…”
Section: Professions As Landscapesmentioning
confidence: 99%